The Effects of an Appropriate Behavior Program on Elementary School Children Social Skills Development in Physical Education - Gil-Madrona, Pedro; Gutiérrez-Marín, Eva Cristina; Cupani, Marcos; Samalot-Rivera, Amaury; Díaz-Suárez, Arturo; López-Sánchez, Guillermo F. (Frontiers in Psychology, 2019)
The purpose of this study was to see the effects of an appropriate behavior development program in relation to the improvement of fair play and social skills behaviors of elementary school children during the physical education class. The participants of this study were 204 students from 5th and 6th grade from 7 different public schools in Castilla La Mancha, Spain. Data was collected through a questionnaire to measure students’ pre-and post-appropriate behaviors to winning, to loosing, during the game, fair play, and social skills during the physical education class. Results from this study revealed that participants improved their behaviors with the implementation of the intervention (appropriate behavior program), generating positive changes in students’ attitudes and social skills during physical education class. In relation to children gender, girls had better scores than boys in relation to appropriate behaviors when losing. Further, when comparing students’ age, those from 10 to 11 years old scored higher in fair play behaviors and social skills. In conclusion, the intervention program was effective to improve the behaviors of the school children, generating positive changes in their attitudes and social skills during physical education.